Efektivitas Permainan Tebak Kata Untuk Meningkatkan Keterampilan Berbicara Siswa Kelas XI Keagamaan Ma Matholi’ul Anwar Simo - azizah, khimayatul; Nur Ifadah, Hastin; ., uwin; ade sofiana, masrifatul (Fakultas Agama Islam, 2024)
Abstract This research is motivated by the low speaking skills of class XI Religious students, this can be seen when habituation to practice speaking skills is less active, students who lack courage in expressing ideas directly and mastery of vocabulary that has not been able to decipher due to lack of intensive speaking practice. In this case, the teacher's role is to provide theory and exercises to hone Arabic language skills. Speaking skills are the ability to express articulated sounds or words to express thoughts in the form of ideas, opinions, desires, or feelings to the interlocutor. In general, speaking skills aim to make students able to communicate orally well and naturally with the language they are learning. In this case, researchers used a cooperative learning method by playing language games, namely guessing words to improve Arabic speaking skills.This research was conducted at MA Matholi'ul Anwar Simo Sungelebak Karanggeneng Lamongan. The objectives are (1) to be able to find out the form of application of word guessing games to improve the speaking skills of grade XI Religious MA Matholi'ul Anwar Simo Sungelebak students, and (2) to find out the effectiveness of word guessing games to improve the speaking skills of grade XI Religious MA Matholi'ul Anwar Simo Sungelebak students. The research design used is pre-experimental type One Group pretest-posttet Design. The population and sample taken by the researcher are the total number of the population used as a sample, namely 43 students. Data collection techniques used include tests, questionnaires, observations and documentation. While the data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. Based on the results of the research obtained, the results of descriptive statistical analysis are the results of learning on the pretest obtained with an average value of 57.79, which is relatively low. While the learning results on the posttest were obtained with an average score of 76.25, which is classified as high. This shows that students' ability in speaking skills after applying the word guessing game has better learning outcomes than before the application of this game. The results of the hypothesis test showed that word guessing games were effective or influential on students' speaking skills in class XI Religious Arabic learning at MA Matholi'ul Anwar. This can be proven by the results of the t-test analysis where at a significant level of 5% if the tcount is smaller than ttable, then H0 is accepted and Ha is rejected, but conversely if tcount is greater than ttable then Ha is accepted and H0 is rejected. From the calculation results obtained t Calculate = 2.567 and t Table = 1.68 then obtained t Calculate > t Table or 2.567> 1.68. so that tcount is greater than ttable, then Ha is accepted and H0 is rejected.